2022
DOI: 10.4314/gmj.v56i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and its demographic, clinical and psychosocial determinants among male patients with hypertension in a Ghanaian tertiary hospital

Abstract: Objectives: This study aimed to evaluate Health-related quality of life (HRQoL) among male patients with hyperten-sion and its associated demographic, clinical and psychosocial factors.Design: This was a facility-based cross-sectional studySetting: This study was carried out at the outpatient department in Korle-Bu Teaching HospitalParticipants: Three hundred and fifty-eight hypertensive patients were recruited for this studyData collection: Information on socio-demographic characteristics, clinical features, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
3
0
1
Order By: Relevance
“…This study investigated the HRQoL of persons living with TB in the Greater Accra Region of Ghana using a globally validated and reliable instrument (WHOQoL-BREF). The WHOQoL-BREF tool was used in this study because it is an internationally accepted and reliable instrument which has been used to assess the HRQoL of persons living with health conditions which impact their quality of life [2] , [6] , [8] , [18] , [29] . The findings can therefore be considered in relation to other persons living with health conditions (such as TB) within comparable settings as Greater Accra, Ghana.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study investigated the HRQoL of persons living with TB in the Greater Accra Region of Ghana using a globally validated and reliable instrument (WHOQoL-BREF). The WHOQoL-BREF tool was used in this study because it is an internationally accepted and reliable instrument which has been used to assess the HRQoL of persons living with health conditions which impact their quality of life [2] , [6] , [8] , [18] , [29] . The findings can therefore be considered in relation to other persons living with health conditions (such as TB) within comparable settings as Greater Accra, Ghana.…”
Section: Discussionmentioning
confidence: 99%
“…The WHOQoL-BREF instrument has been used globally as a valid and reliable tool for the assessment of the HRQoL of persons living with TB [8] , [10] , [29] . The WHOQoL-BREF QoL tool has also been used for its validity among the Ghanaian adult population [2] , [4] , [6] . The WHOQoL-BREF QoL instrument was found to have acceptable reliability since an overall Cronbach’s alpha coefficient of 0.95 was recorded in this study [20] .…”
Section: Methodsmentioning
confidence: 99%
“…(50) La edad más avanzada y ciertas comorbilidades afectan el sistema locomotor, lo cual limita la actividad física relacionada con las actividades domésticas y laborales. (51) En cuanto a las otras dimensiones, observamos que, en sus resultados presentan niveles promedio, alto y muy alto, esto se debe a que, un conocimiento insuficiente sobre la hipertensión y sus cuidados podría conducir a un control de la PA sistólica menos óptimo, lo cual puede reflejarse en tasas más bajas de adherencia a los medicamentos antihipertensivos prescritos y al compromiso con prácticas de estilo de vida saludables. El manejo de la patología determina la condición y percepción que uno tendrá de su salud que ha demostrado promover un control idóneo de la PA y evitar las complicaciones resultantes de la PA alta.…”
Section: Discussionunclassified
“…Particularly in low-and middle-economy countries such as China, Brazil, India and Mexico, where the economic burden of LCA and HT together contribute to 50 % of the total number of economic estimates identified (2) In Latin American countries, the prevalence of hypertension is high, with the countries with the highest prevalence being Brazil with 25-35 %, Paraguay with 34 %, Chile with 33,7 %, Uruguay and Venezuela with 33 %; also, in Colombia by 25 % (3) It is estimated that, by 2025, the figure could increase to 60 % reaching a figure of 1 560 000 000 individuals globally (4) Health-related quality of life (HRQOL) is a concept commonly used in the subjective assessment of a patient's health that reflects the patient's physical, psychological, social and emotional well-being as it is closely related to Health-related quality of life (QoL) and can cause an impact on their health status. (5,6) However, hypertension negatively affects patient QoL especially in older people, who have more health care needs and are more likely to have worse HRQOL than healthy people (7,8) For hypertensive patients, risk factors originate in two ways, the non-modifiable ones that are age, sex and genetics, which are aspects that are already established in humans; on the other hand, there are modifiable ones related to the habits and behaviors adopted in the lifestyle, the 12 which are food, the consumption of harmful substances and sedentary lifestyle (9,10) Therefore, improving lifestyle, making healthy habits, adequate adherence to treatment and maintaining positive mental health will allow hypertensive patients to avoid or reduce risk factors that may have consequences on their health well-being (11,12) In a study conducted in Poland, with participants between the ages of 30 to 89 years, they stated in their results that, the Health-related quality of life of people who were mostly men had a medium and good Healthrelated quality of life, concluding that healthy behaviors, follow the treatment properly and periodically take their blood pressure, towards keeping people's Health-related quality of life healthy (13) In a study conducted in Pakistan, with 384 hypertensive participants, they observed in their results that, most of the participants were male, 56 % of them had a poor Health-related quality of life related to health between the ages of 41 to 50 years, concluding that by not making healthy habits for the management of their disease, tended to have an inadequate Health-related quality of life (14) In a study carried out in Angola, with 113 participants, they stated in their results that, with respect to hypertensive participants, 64,6 % of them had a regular Health-related quality of life and 35,4 % a poor Healthrelated quality of life, concluding that the conditions and difficulty in accessing health services aggravate the disease due to factors such as overcrowding, inadequate feeding and poor living conditions (15) Therefore, the research objective is to determine the health-related quality of life in relation to health in hypertensive regular basic education teachers...…”
Section: Introductionmentioning
confidence: 99%